Emerging and Established Histological Techniques for the Analysis of Thrombosis in COVID-19 Lungs - Spier, Addie B.; Evans, Colin E. (Frontiers in Cardiovascular Medicine, 2021)
Coronavirus disease 2019 (COVID-19) is the potentially lethal disease that is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Patients with COVID-19 have an increased risk of thrombosis, but the role of thrombosis in the pathogenesis and progression of severe COVID-19 remains unclear. A better understanding of the contribution of thrombosis to the development and progression of COVID-19 could lead to the development of novel COVID-19 treatments. For this reason, established and emerging histological techniques have recently been used to analyze COVID-19 lungs quantitatively and visually and in two and three dimensions. The gold standard and novel state-of the-art histological techniques that have been used to assess thrombosis in COVID-19 lungs are described in this Mini Review.